Minimally Invasive Complete Mouth Reconstruction using Full-Contour Ceramic Veneers: A Clinical Report - Butler, Sheila; Torrealba, Ysidora (Puerto Rico Health Sciences Journal, 2018)
This case report illustrates a full-mouth rehabilitation for a patient that presented with severe non-carious tooth surface loss. The patient was restored following a minimally invasive tooth preparation, with 28 full-contour veneers. The patient was evaluated at baseline and at 2, 9, and 13 months following cementation to assess the integrity of the restorations, the proximal and occlusal contacts, pulp vitality, and tooth mobility. After 13 months, no postoperative sensitivity was reported. In addition, no secondary caries, loss of tooth vitality, or chipping or fractures of the veneers were detected. The clinical outcome of using a minimally invasive adhesive technique was an esthetic, mechanical, and biological success.